2016
DOI: 10.3892/etm.2016.3333
|View full text |Cite
|
Sign up to set email alerts
|

Antiosteoporotic effect of icariin in ovariectomized rats is mediated via the Wnt/β-catenin pathway

Abstract: Icariin (ICA), the main active flavonoid glucoside isolated from Herba Epimedii, has been shown to prevent postmenopausal bone loss in vitro. However, the mechanisms by which ICA prevents bone loss in vivo remain poorly understood. In the present study, the effect of ICA in an ovariectomized (OVX) rat model of osteoporosis was evaluated. Sprague-Dawley rats were divided into sham-operated and OVX groups. The OVX rats were randomly divided into five groups: OVX group (water only), Fosamax (positive) group (5.04… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 30 publications
0
47
0
Order By: Relevance
“…FE increased OPG protein expression and reduced the RANKL protein expression in OVX rats (18). Icariin increased the mRNA expression ratio of OPG/RANKL, up-regulated mRNA expression of low-density lipoprotein receptorrelated protein 6 (Lrp6) receptor, while it downregulated glycogen synthase kinase-3β and Runx2, following OVX (24,25). Icariin was also found to upregulate expression of bone morphogenetic protein 2 (BMP2), BMP4, Runx2, osteocalcin, Wnt1, and Wnt3a in OPG knockout mice, and increase the expression of the direct target genes of β-catenin signaling such as AXIN2, dickkopf-related protein 1 (DKK1), T cell factor 1 (TCF1), and lymphoid enhancer-binding factor 1 (LEF1) (26).…”
Section: In Vivo Findingsmentioning
confidence: 99%
“…FE increased OPG protein expression and reduced the RANKL protein expression in OVX rats (18). Icariin increased the mRNA expression ratio of OPG/RANKL, up-regulated mRNA expression of low-density lipoprotein receptorrelated protein 6 (Lrp6) receptor, while it downregulated glycogen synthase kinase-3β and Runx2, following OVX (24,25). Icariin was also found to upregulate expression of bone morphogenetic protein 2 (BMP2), BMP4, Runx2, osteocalcin, Wnt1, and Wnt3a in OPG knockout mice, and increase the expression of the direct target genes of β-catenin signaling such as AXIN2, dickkopf-related protein 1 (DKK1), T cell factor 1 (TCF1), and lymphoid enhancer-binding factor 1 (LEF1) (26).…”
Section: In Vivo Findingsmentioning
confidence: 99%
“…Moreover, icariin inhibited osteoclast differentiation and bone resorption by suppression of MAPKs/ NF‐κB . The recent study showed that icariin has strong osteogenic activity, inducing osteogenic differentiation and inhibiting resorption by osteoclasts in ovariectomized rats …”
mentioning
confidence: 99%
“…In the ASB16-AS1 centered network, gene CTNNB1 encodes β-catenin protein which can aggregate and move into the nucleus and then can active wnt/β-catenin signaling pathway. The target gene of β-catenin protein, RUNX2 , is active to promote osteoblast proliferation and differentiation [5153]. Interestingly, these genes which mainly play roles in osteoblasts, were found to be co-expressed with ASB16-AS1 in PBMs which are precursors of osteoclasts [33].…”
Section: Discussionmentioning
confidence: 99%